Molecular-dynamic calculation of the inverse-bremsstrahlung heating of non-weakly-coupled plasmas - David, N; Spence, D; Hooker, S (2004)
The inverse bremsstrahlung (IB) heating rates of a plasma as a function of density and laser intensity were calculated using a molecular dynamic (MD) code. The code belonged to the class of particle-particle-particle-mesh codes. The equations solved by the MD code avoided several assumptions which were inherent to alternative methods. The results of the MD code were compared to previous results for plasmas of low coupling. The results of the calculations for dense, moderately coupled plasmas were also presented. An analytic expression for the IB heating rate, based on a fit to the rates calculated by MD code, was also presented.